PATRIARCHY UNVEILED: A FEMINIST ANALYSIS OF RESISTANCE AND EMPOWERMENT IN MANJU KAPUR’S A MARRIED WOMAN (Al-Aasar, 2025)
This research offers a feminist analysis of Manju Kapur’s A Married Woman, exploring the nuanced themes of resistance and empowerment within the patriarchal structures that define the lives of its central characters. It examines how the protagonist, Astha, navigates the limitations imposed by gendered expectations, societal norms, and marital constraints in her quest for self-identity and autonomy. It focuses on the tension between traditional roles of wife and mother and the desire for personal freedom, highlighting the internal and external forces that shape Astha’s journey of resistance. By focusing on her relationships, sexual autonomy, and spiritual awakening, the paper demonstrates how Kapur portrays both the oppressive nature of patriarchy and the transformative potential of feminist consciousness. Findings indicate that women struggle to assert their autonomy under patriarchy, acknowledging the obstacles they face in patriarchal societies while also recognizing their capacity for resistance and self-actualization.